Eksistensi Etika Profesi Guru di Masa Sertifikasi: Problem dan Solusinya - Siti Asiah (Turats, 2009)
Ethic is one of the aspect of education. Ethics (via Latin ethica from the Ancient Greek "moral philosophy", from the adjective of ēthos "custom, habit"),is the study of values and customs of a person or group. It covers the analysis and employment of concepts such as right and wrong, good and evil, and responsibility. This article describes about teacher ethical profession as the urgent of dimension in the era of teacher sertivication as explained in the Law of Teacher and Lecturer and in The Law of National Education System. From this topic we know that morals (akhlaq): these consist of the commands and teaching relating to the spiritual and moral characteristics of human beings, such as justice, fear of God (taqwa), courage, chastity, wisdom, endurance, loyalty, truthfulness, truth worthiness, etc., and prescribe ‘how’ human being should be. Things that relate to human qualities are called akhlaq.The aspect of moral and ethic is very important of education because one goal of education is to perfect of morality.